Robotic versus laparoscopic pancreaticoduodenectomy for pancreatic and periampullary tumors: a meta-analysis - Tang, Gang; Chen, Fang; Chen, Rui (Frontiers in Oncology, 2024)
ObjectiveThe value of robotic pancreaticoduodenectomy (RPD) compared with laparoscopic pancreaticoduodenectomy (LPD) for pancreatic and periampullary tumors is controversial. This study aims to assess the available literature and compare the short outcomes of RPD and LPD.MethodsThe PubMed, Cochrane Library, Embase, and Web of Science databases were searched to identify available research published up to 24 July, 2024. Risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) were calculated.ResultsSeventeen studies with a total of 9417 patients (RPD group: 3334 patients; LPD group: 6083 patients) were included in this meta-analysis. The RPD group had lower overall morbidity (RR, 0.79), conversion (RR, 0.29) and blood transfusion rates (RR, 0.61), shorter length of stay (MD, -0.72 days), and higher number of harvested lymph nodes (MD, 0.62) than the LPD group. There were no significant differences in 90-day mortality (RR, 0.89), major complications (RR, 0.87), operative time (MD, -3.74 mins), blood loss (MD, -24.14 mL), reoperation (RR, 0.94), bile leak (RR, 0.62), postoperative pancreatic hemorrhage (RR, 0.96), postoperative pancreatic fistula (RR, 0.74), delayed gastric emptying (RR, 1.24), and R0 resection (RR, 1.00) between the groups.ConclusionsCompared with LPD, RPD for pancreatic and periampullary tumors could be safe and effective, and it has superior surgical outcomes. Further randomized controlled trials to verify the potential advantages of RPD over LPD are necessary.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=581133, identifier CRD42024581133.